Bibliometric analysis of the academic production on Geodiversity and related themes in the Federal Universities of Brazil - José Francisco de Araújo Silva; Marcos Antônio Leite do Nascimento; Eduardo Adriani Rapanos (Terr@ Plural, 2022)
Research on geodiversity has been increasing in recent years, both internationally and in Brazil. This theme refers to the abiotic elements of the planet and has been the subject of studies since the 1990s, having developed nationally in the early 2000s. This work analyzed the academic research on geodiversity and related themes carried out in Brazil from 2000 to 2021, through a systematic search and bibliometric research in libraries, institutional repositories, and digital collections of the 69 Brazilian Federal Universities (HEI) and in the Brazilian Digital Library of Theses and Dissertations (BDTD). We searched the terms ‘geodiversity’, ‘geoconservation’, ‘geoconservationist/s’, ‘geotourism’, ‘geopark/s’, ‘geopatrimony’, ‘geosite/s’, and ‘geological heritage’. It was found 209 papers in 36 universities distributed in all regions of the country, with emphasis on the Northeast region, with 73 research in 9 institutions, followed by the Southeast region (65 papers in 12 HEIs), South (51 papers in 6 HEIs), Center-West (13 research in 6 HEIs) and North (7 publications in 4 HEIs). Regarding the number of papers, the Federal Universities of Minas Gerais (25), Pernambuco (20), Ceará (18) and Rio Grande do Sul (16) stand out, with the predominant being Dissertations (106), followed by Theses (57) and Final Papers (46). Written since 2003, there was a significant increase as of 2012, with 2016 standing out, and a decrease in 2020. Regarding the frequency of use of the keywords selected in the research, ‘geodiversity’ and ‘geoconservation’ prevailed. We highlight the master’s and doctoral courses in Geography, and undergraduate courses in Geology